Viruses and their effect on human chromosomes - Renda, Yavuz (The Turkish Journal of Pediatrics, 1968)
This investigation was performed in order to study the effect of nononcogenic viruses on human chromosomes. Measles, chickenpox and mumps cases were selected and peripheral leukocyte cultures were obtained for chromosomal analyses. These cases showed significantly higher amounts of structural anomalies than the control group. The results and the pathogenesis of this phenomenon are discussed.